`3/5x+4/3=[-4]/3`
`3/5x=[-4]/3-4/3`
`3/5x=[-8]/3`
`x=[-8]/3:3/5`
`x=[-8]/3xx5/3=[-40]/9`
\(\dfrac{3}{5}x+\dfrac{4}{3}=\dfrac{-4}{3}\\ \dfrac{3}{5}x=\dfrac{-4}{3}-\dfrac{4}{3}=-\dfrac{8}{3}\\ x=-\dfrac{8}{3}:\dfrac{3}{5}=-\dfrac{40}{9}\)
\(\dfrac{3}{5}x=-\dfrac{4}{3}-\dfrac{4}{3}\)
\(\dfrac{3}{5}x=-\dfrac{8}{3}\)
\(x=-\dfrac{8}{3}:\dfrac{3}{5}\)
\(x=-\dfrac{8}{3}\times\dfrac{5}{3}\)
\(x=-\dfrac{40}{9}\)
`3/4 x + 4/3 = -4/3`
`3/5x = -4/3 - 4/3`
`3/5x = -8/3`
`x = -8/3 : 3/5`
`x = -40/9`
\(\dfrac{3}{5}x+\dfrac{4}{3}=\dfrac{-4}{3}\)
\(\dfrac{3}{5}x=\dfrac{-4}{3}-\dfrac{4}{3}\)
\(\dfrac{3}{5}x=\dfrac{-8}{3}\)
\(x=\dfrac{-8}{3}:\dfrac{3}{5}\)
\(x=\dfrac{-8}{3}\cdot\dfrac{5}{3}\)
\(x=-\dfrac{40}{9}\)